2015
DOI: 10.1093/cid/civ396
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment Outcomes of Patients Infected With Hepatitis C Virus: A Systematic Review and Meta-analysis of the Survival Benefit of Achieving a Sustained Virological Response

Abstract: The results of this meta-analysis suggest that there is a significant survival benefit of achieving an sustained virologic response compared with unsuccessful treatment in the general hepatitis C virus-infected population. This benefit is held in patients with cirrhosis and those coinfected with human immunodeficiency virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
183
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(198 citation statements)
references
References 54 publications
9
183
1
5
Order By: Relevance
“…S3 and S4). Studies on interferon and ribavirin treatment for chronic HCV infection have reported that all-cause mortality rates for patients with a sustained virological response-which equates to cure in nearly all cases-are not statistically different from those of an age-matched general population (12)(13)(14). Therefore, we used general-population mortality rates as a proxy for patients who receive new HCV-directed therapies (15,16).…”
Section: Simulating An Hcl Fundmentioning
confidence: 99%
“…S3 and S4). Studies on interferon and ribavirin treatment for chronic HCV infection have reported that all-cause mortality rates for patients with a sustained virological response-which equates to cure in nearly all cases-are not statistically different from those of an age-matched general population (12)(13)(14). Therefore, we used general-population mortality rates as a proxy for patients who receive new HCV-directed therapies (15,16).…”
Section: Simulating An Hcl Fundmentioning
confidence: 99%
“…It is notable that groups B and C might include patients without chronic liver diseases before the occurrence of HCC. Nevertheless, when focusing only on effects in viral-related cases, group A comprised of more patients with a history of anti-viral therapy and had a more advantageous hepatic reserve (13,14). Moreover, an earlier stage of HCC and stable hepatic reserve, which were related with regular hospital visits before occurrence of HCC, might be more amenable to curative initial treatments for HCC and contribute to an improved prognosis after the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study examined the survival benefit of achieving SVR, looking at a total of 33,360 patients with HCV and HIV/HCV coinfection [31]. Achieving HCV SVR was associated with a 50% reduction in the risk of all-cause mortality compared with not achieving SVR in the general HCV population.…”
Section: Coinfection With Hivmentioning
confidence: 99%